A Literature Review on Precision Data, Political Economy, and Digital Culture - Usmany, Paul; Usmany, Alfrin Ernest Marthen; Ariyanto, Komang (Jurnal Sosialisasi: Jurnal Hasil Pemikiran, Penelitian dan Pengembangan Keilmuan Sosiologi Pendidikan, 2024)
Precision data plays a crucial role in shaping public policies, which have a positive impact on economic dynamics and social structures. Fostering an inclusive and thriving digital culture enhances communication and public participation in political and economic processes, leading to better decision-making that is responsive to people's needs. This article aims to explore the relationship between precision data, political economy, and digital culture, and how the utilisation of precision data influences the dynamics of political economy within digital culture. It aims to understand how data and new technologies influence village development, rural revitalization, and communication in the digital era. The research employs a literature review method, analyzing previous relevant research articles. The findings demonstrate that Digital Development Precision can effectively assess and analyse indicators of the achievement of Sustainable Development Goals in rural areas. There is also a strong correlation between markets and politics, which shape political actions and incentives. Market structures significantly impact political behaviour. Within the context of rural revitalization, big data has accelerated change by digitising rural development communication, bringing about improvements in various aspects of rural society and transforming the pattern of political communication through social media platforms. This transformation enables effective communication with target audiences.